Adoption of Six Sigma DMAIC to reduce cost of poor quality. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this paper is to demonstrate the systematic application of Six Sigma tools for identification and reduction of cost of poor quality (COPQ). The study examines one of the chronic problems of failure of cooling fan assembly at repair division of a company dealing in helicopter components.Design/methodology/approach – The case adopted Six Sigma Define‐Measure‐Analyze‐Improve‐Control (DMAIC) methodology to achieve the goal of reduction in COPQ.Findings – After completing the Define, Measure and Analyze phase, it was found that use of extreme tolerances and cross‐fitment of bearings are the root cause of cooling fan assembly failure. The major recommendations made during the Improve phase were to design a bearing matching software for improving the cross‐fitment of bearings and to procure a hydraulic jig with electronic jig instead of manual jig. The value of implementing these recommended solutions equate to a saving of INR 34 lacs per annum. Since it was a chronic problem, the company expects this to be a recurring saving.Originality/value – This specific case exhibits the successful application of Six Sigma DMAIC methodology in repair and maintenance for driving down the cost of failure and improved processes.